Brand Experience dan Brand Loyalty: Mediated by Brand Trust - Saptaningsih Sumarmi; Hety Wijayanti (Universitas Mercu Buana, 2023)
Brand loyalty is a company's goal to gain recognition from the community, so it becomes a challenge for companies to make customers loyal to a brand. This study will investigate the relationship between brand experience and brand loyalty, using brand trust as a mediation. The research respondents were 150 users of Kutus-kutus oil in DIY. The research data were analyzed using PLS-SEM. The results show no direct relationship between brand experience and brand loyalty. However, brand experience is related to brand trust, and brand trust is directly related to brand loyalty. Indirectly, brand experience is related to brand loyalty mediated by brand trust. Limitations/implications of the study: The research was conducted in the same province as the Special Region of Yogyakarta, so the generalization of the results had to be determined by completing additional studies elsewhere